Cystic calculi removal in African spurred tortoise (Geochelone sulcata) using transplstron coeliotomy - Che' Amat, Azlan; Among, Benny Gabriel; Ng, Wen Chee (Veterinary World, 2012)
The present report was carried out to manage a case of calculi in the bladder of African spurred tortoise. A 6 year old African spurred tortoise presented with history of anorexia and whitish discharged from the vent. Upon physical examination, the tortoise were 10% dehydrated, hindlegs muscle wasting and whitish materials came out from the vent. Plain radiograph revealed increased radiopacity in the bladder and also both right and left kidney. Contrast gastrointestinal radiograph showed less possibility of foreign body. Inconclusive radiological findings required the decision to proceed with exploratory transplastron coeliotomy by using dental burr. About 4 cm solid, hard whitish mass was removed from the bladder and both kidney was congested with whitish material. The findings were suggestive for urates crystal calculi based on histology result